Nutrição de operárias de uruçu-amarela, Melipona flavolineata Friese, 1900 (Apidae: Meliponina) - COSTA, Luciano (Universidade Federal do Pará, 2011)
Stingless beekeeping is an old practice in the Americas. However, the activity is still undeveloped, requiring management techniques improvements. This study evaluated nutritional alternatives for the Amazonian stingless bee Melipona flavolineata, looking for a food replacement for honey and fermented pollen. The following food replacement were compared to honey (T1): inverted sugar syrup with minerals (T2), inverted sugar syrup with amino acids and vitamins in the following concentrations: 0.5% (T3), 1.0% (T4) and 10% (T5). It was compared to fermented pollen (T1), fermented foods with inoculum of fermented pollen of M. flavolineata consisting of: commercial pollen of A. mellifera (T2); brewers yeast (T3), and soybean extract in two different concentrations of proteins (T4, 12%; and T5, 18%). The nutritional value of the diet was based on the daily intake, on the weight of workers, on the size of hypopharyngeal glands acini and on the size of oocytes. The cost of the ingredients of the diets was also evaluated. The results showed that among the alternatives to honey, there were no significant differences between the control and all treatments. Differences were found only between the sizes of acini of workers that were fed by treatments 2 and 4, in which treatment 4 was superior. The costs of ingredients indicated the treatment 2 as cheaper than the others. Among the alternatives to the fermented pollen, larger differences were found. Consumption of treatment 4 was significantly higher than treatment 3, indicating a greater acceptance of soybean extract in relation to yeast. For other parameters evaluated, treatment 5 was superior to all others and its cost was much lower than the T2 and similar to T3 and T4. We concluded that the best alternative for the nutrition of M. flavolineata are the sugar inverted syrup with minerals, and semi-artificial fermented pollen based in soybean extract (T5, 18% proteins). Newly formed colonies, having 500-600 bees, must receive 10 to 20 ml of syrup and 25 g of semi-artificial fermented pollen weekly.